Determination of Anti-Diabetic Activity of Gynura Procumbens Using Bioassay–Guided Fractionation - Mohd Bohari, Siti Pauliena (2006)
This study aims to investigate the antidiabetic and hypoglycaemic properties of Malaysian herb, Gynura procumbens (Sambung nyawa). Bioassay guided fractionation has been carried out to identify the bioactive crude fraction responsible for antidiabetic activity of Gynura procumbens. Both in vitro and in vivo model study were used to evaluate the antidiabetic properties of this plant. In vitro insulin secretion study, glucose uptake study and cytotoxicity were used as primary assay on crude methanolic extract, hexane, ethyl acetate and butanol fractions. Cytotoxicity studies demonstrated that crude methanolic extract have the lowest cytotoxicity when compared with crude fractions Gynura procumbens in BRIN BD11 cell lines. Cytotoxicity study with adipocytes and muscle cell lines showed that the crude methanolic extract of Gynura procumbens have the lowest toxicity when compared with the crude fractions of the plant. Determination of insulin secretion response was done by using BRIN BD11 cell lines and from the result, it showed that crude hexane and ethyl acetate crude fractions have good potential in stimulation of insulin release. Glucose uptake study with adipocytes cell lines (3T3 mouse adipocytes cell lines) indicated that this plant has the dose dependent manner and Gynura procumbens crude hexane fraction indicated the highest activity on stimulating glucose uptake. Effect of crude methanolic extract and crude fractions in the presence of insulin showed moderate glucose uptake activity when compared with Gynura procumbens crude extract/ fractions alone. Glucose uptake study with a mouse L6 muscle cell lines indicated that Gynura procumbens crude methanolic extract has highest reading from all of the crude extracts. When comparing the crude extract and fractions with insulin, all of the results showed moderate glucose uptake activity and thus expressed that this plant has dose dependent manner. Further study was done with Type 1 and Type 2 model diabetic rats. It shows that crude methanolic extract of Gynura procumbens have hypoglyceamic activity on both models. This result was further investigated with gut perfusion study using crude methanolic extract and ethyl acetate fraction of Gynura procumbens and showed positive result by delaying glucose absorption in the rat intestine.Further investigation was done with ethyl acetate fraction that showed potential activity from In vitro and In vivo study. Identification of compounds by using reverse phase HPLC showed some promising peaks of interesting compounds. Isolation and purification was carried on by using various chromatography techniques such as normal chromatography and gel filtration Sephadex LH-20. Two compounds from isolated from ethyl acetate fraction were mix of β-sitosterol and stigmasterol, and kaemferol-3-O- glucoside.